Synthetic Pathways of trans-Substituted Porphyrins Bearing Pentafluorophenyl Groups from Dipyrromethanes - Milena B. Boarini; Daniel A. Heredia; María E. Milanesio; Edgardo N. Durantini (Chemistry Proceedings, 2024)
Different approaches were evaluated to obtain 5,15-bis [4-(N,N-diphenyl)aminophenyl]-10,20-bis(pentafluorophenyl)porphyrin and 5,15-bis [4-(9-carbazolyl)phenyl]-10,20-bis(pentafluorophenyl)porphyrin. First, the reaction of 5-pentafluorophenyldypyrromethane with the corresponding benzaldehyde catalyzed by boron trifluoride diethyl etherate in dichloromethane led to a high level of scrambling that produced a mixture of porphyrins. These products involve ABAB (3%), A3B (15%), and A4 (4%) symmetries, where A represents a pentafluorophenyl group. These porphyrins have similar polarities and they are very difficult to separate by column chromatography. Therefore, the reagents were changed to pentafluorobenzaldehyde and dipyrromethane. When a 0.5:1 molar ratio was used, A4 porphyrin was not obtained, and the main products were ABAB (19%) and A3B (6%). Therefore, condensation of a dipyrromethane with pentafluorobenzaldehyde provides a general method for the rational synthesis of ABAB-porphyrins in good yield with lower scrambling.